Improving the performance of a Publish-Subscribe message broker - Rocha, Rafael (2019)
The Arrowhead Framework, a SOA-based framework for IoT applications, provides the Event Handler system: a publish/subscribe broker implemented with REST/HTTP(S). However, the existing implementation of the Event Handler suffers from message latency problems that are not acceptable for industrial applications. Thus, this paper describes the refactoring process of this system that enabled it to reach acceptable levels of latency.